PRODUCTIVITY OF ELEPHANT GRASS (Pennisetum purpureum) PLANTED WITH LEGUMINOSE AT VARIOUS DOSAGES OF BIOORGANIC FERTILIZER - N. G. K., RONI; LINDAWATI, S. A.; DEWI, P. J. N. (Majalah Ilmiah Peternakan, 2024)
The purpose of this study was to determine the productivity of elephant grass (Pennisetum purpureum) planted with leguminosae at various doses of bioorganic fertilizers. This study used a completely randomized design with two factorial patterns. The first factor was the type of leguminosae (T= without leguminosae; R= Arachi pintoi; L= Alysicarpus vaginalis; and the second factor was the dose of bioorganic fertilizer (D0= 0 kg Nha-1; D1= 100 kg Nha-1; D2= 200 kg Nha-1; and D3= 300 kg Nha-1) There were 12 treatment combinations, each treatment was repeated 5 times so that it consisted of 60 experimental units. The observed variables included growth, yield and growth characteristics variable. The results showed that there was no interaction between leguminous species and fertilizer dosage, both leguminous species only increased leaf area per pot, bioorganic fertilizer D1 and D2 doses tended to increase, while D3 dose increased leaf dry weight, total forage dry weight, and leaf area per pot of elep- hant grass (Pennisetum purpureum). It was concluded that the type of leguminous did not affect the productivity of elephant grass, the dose of bioorganic fertilizer increased crop yields, the highest yields at a dose of 300 kg Nha-1 bioorganic fertilizer.